Budheting and accounting reforms within the public financial mangement framework: the Portuguese case - Jorge, S. M.; De Jesus, M. A. J. (Retos de la contabilidad y la auditoría en la economía actual, 2018)
This chapter discusses the role of budgetary and accounting systems within the Public Financial Management (PFM) framework. Additionally, it describes the reforms nowadays taking place in Portugal, namely taking into consideration new budgetary and accounting systems starting implementation, explaining how they are included in a broader reform of the PFM structure. PFM implies governments to use integrated systems to allocate funds and control spending execution, involving a wide approach, including policies design and internal and external auditing assessment systems. Also accounting reforms are essential to achieve PFM purposes, namely applying accrual basis to prepare and report financial statements under the international accounting standards approach (Lawson, 2015). In Portugal, in the latter years, within the public sector, there has been a great fragmentation of accounting and reporting systems applied to different entities, raising inconsistencies and creating difficulties when trying to assess the Whole of Government financial condition. In this context, the Portuguese government, under strong recommendations of the loaners (because of the financial assistance through Troika), started a set of PFM reforms, including changing the existing public sector accounting system by adopting the International Public Sector Accounting Standards (IPSAS) as the benchmark (Nogueira et al., 2017). Accordingly, in 2015 relevant legislation was issued: the new Budgetary Framework Law (LEO – Law 151/2015) and the new System of Accounting Standards for Public Administrations (SNC-AP – Law-decree 192/2015). In 2016 a unit to assure the implementation of these new budgetary and accounting systems was created, designated as UniLEO. According to Viana (2017), the mission of this unit configures a true PFM reform. Hereafter, the chapter is organised in four sections. Section 2 addresses the harmonization problems related to accounting reforms in financial accounting and their inclusion in a broader reform process under PFM objectives. Section 3 explains the benefits of integrating budgetary and financial accounting innovations in a broader PFM reform, also highlighting how PFM systems outputs could be used to change the EU convergence criteria framework. The Portuguese PFM reforms, including budgeting and accounting changes, presently being implemented, are described in Section 4. In Section 5 some final marks and conclusions are synthesised, highlighting the Portuguese PFM reforms as a reference at an international level.